Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Construction of bioaffinity antibacterial coatings via piezoelectric effect-enhanced alkaline microenvironment - Zhe Hao; Cong Wu; Ning Zhao; Ran Liu; Guolu Mu; Yufei Tang (Chemical Engineering Journal, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Transglutaminase modification improved water holding capacity and quality characteristics of Lactiplantibacillus plantarum AHQ-14 fermented milk - Yanshu Hu; Xiao Cong; Lai Jiang; Guangqing Mu; Shujuan Jiang (International Dairy Journal, 2026)

Bidirectional aeolian erosion controls the spatial variations of yardang landforms in Dunhuang yardang National Geopark, Northwestern China - Yongchong Lin; Chunyao Wu; Guijin Mu; Jifeng Zhang; Cong Zhao (Aeolian Research, 2026)

Climatological characterisation and trends of extreme winds and their application to power transmission lines in China - Hongyu Wang; Cong Jiang; Feifei Mu; Kai Liu; Rui Mao; Xin Yin (Natural Hazards, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Spatio-temporal distribution characteristics and sources of organic carbon in a typical mariculture Bay: A case study of Sansha Bay, China - Xiaolong Lv; Lingyi Lei; Feipeng Wang; Rongmao Li; Cong Li; Hua Lin; Zhi Zhang; Jingli Mu (Marine Environmental Research, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

The importance of fungal necromass in soil organic carbon: Insights from elevation gradients in arid regions - Mengfei Cong; Zhihao Zhang; Guangxing Zhao; Xinping Dong; Yan Lu; Lei Li; Yang Hu; Weiqi Wang; Zhaobin Mu; Akash Tariq; Jordi Sardans; Josep Peñuelas; et al. (Applied Soil Ecology, 2025)

Interlayer covalent bridging covalent organic polymers for highly efficient photocatalytic organic synthesis - Xia Zhao; Ai-Cen Li; Dan Yang; Yong-Hui Wang; Xin Mu; Cong Wang; Hua-Qiao Tan (Chemical Engineering Journal, 2025)

Evaluating the green development level of marine molluscan shellfish aquaculture industry and analyzing obstacle factors that hinder its improvement: The case of China - Runsheng Pei; Hongzhi Zhang; Zifei Liu; Cong Yu; Yingxue Zhang; Yongtong Mu (Aquaculture, 2025)

The driving effect of marine industries on marine pollution: Empirical evidence from coastal China - Cong Yu; Zifei Liu; Xianghui Kong; Runsheng Pei; Wanchanok Umprasoet; Yongtong Mu; Jun Xu (Journal of Cleaner Production, 2025)

Soil minerals regulate soil organic carbon accumulation through glomalin-related soil protein along an elevation gradient in a mountain arid ecosystem - Guangxing Zhao; Zhihao Zhang; Weiqi Wang; Mengfei Cong; Xinping Dong; Yanju Gao; Zhaobin Mu; Yan Lu; Lei Li; Akash Tariq; Jordi Sardans; Josep Penuelas; et al. (Environmental Research, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Eco-friendly chitosan microspheres as a novel one-step sorbent for the rapid purification and determination of pesticides and veterinary drug multi-residues in aquatic products with HPLC-MS/MS - Ruidong Zhou; Yupeng Wen; Wendi Huo; Cong Kong; Guangxin Yang; Huan Liu; Chaoying Zhang; Yingchun Mu; Dongmei Huang; Jincheng Li (Food Chemistry, 2025)

Enhancing immune defense against COVID-19: Alveolar delivery of mucosal vaccines - Pei-Huang Wu; Dong-Chun Hong; Chu Xie; Mu-Sheng Zeng; Cong Sun (Science Bulletin, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Vegetation factors and atmospheric dryness regulate the dynamics of ecosystem water use efficiency in a temperate semiarid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Xulin Guo; Shaorong Hao; Tianshan Zha; Yuqing Zhang; Cong Han; Shengjie Gao; Fei Xing; Shugao Qin; Peng Liu; et al. (Journal of Hydrology, 2024)

Dry-season length affects the annual ecosystem carbon balance of a temperate semi-arid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Tianshan Zha; Xulin Guo; T. Andrew Black; Yuqing Zhang; Shaorong Hao; Cong Han; Shengjie Gao; Shugao Qin; Peng Liu; et al. (Science of The Total Environment, 2024)

Elucidation of the neutralizing antibody evasion of emergent SARS-CoV-2 Omicron sub-lineages using structural analysis - Cong Sun; Yuan-Tao Liu; Yin-Feng Kang; Chu Xie; Shu-Xin Li; Yu-Tong Lu; Mu-Sheng Zeng (Science China Life Sciences, 2023)

Study on the inhibitory effect and mechanism of perfluoro(2-methyl-3-pentanone) on the combustion of gasoline blended with biomass additives - Xuemeng Mu; Haiyong Cong; Ziqi Yuan; YuBo Bi; Mingshu Bi (Fuel, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

Bone marrow mesenchymal stem cell-derived exosomes loaded with miR-26a through the novel immunomodulatory peptide DP7-C can promote osteogenesis - Shuang Lai; Li Deng; Cong Liu; Xinlun Li; Liyuan Fan; Yushu Zhu; Yiling Yang; Yandong Mu (Biotechnology Letters, 2023)

Value-added utilization of hydroxy-substituted aromatics in coal-derived liquids - Zhi-Hao Ma; Sheng Li; Xue-Qian Dong; Cai-Xia Ju; Dan Mu; Zheng Yang; Min Li; Xian-Hou Guo; Zhi-Min Zong; Xing-Shun Cong; Xian-Yong Wei (Fuel, 2023)

Performance and changes of high‐resolution (1 km) surface air temperature in Northern Hemisphere permafrost regions - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yaohua Zhao; Xuanjia Li; Weiwei Tian; Cong Chen; Benben Liang; Xiaodong Li; Cuicui Mu (International Journal of Climatology, 2023)
Surface air temperatures are significant indicators of environmental and climatic change that affect a diverse set of physical systems including permafrost. Most temperature products, such as gridded or reanalysis data, are still at a relatively low spatial resolution, limiting the ability to simulate heterogeneous permafrost changes and leading to large uncertainties. Here we apply a downscaling method based on elevation to obtain high‐resolution surface air temperatures from the sixth Coupled Model Intercomparison Project in Northern Hemisphere permafrost regions. Root‐mean‐square errors and mean absolute errors after downscaling are reduced by 34 and 37%, respectively, relative to meteorological site data and gridded observations from the Climatic Research Unit. Compared to the downscaled surface air temperature data, nondownscaled model projections overestimate by 0.12–0.39°C in the discontinuous, isolated, and sporadic permafrost regions and underestimate up to 0.18°C in the continuous permafrost region under different emission scenarios. The warming rates in Northern Hemisphere permafrost regions were 0.093°C/10 year during the historical (1850–2014) period and are projected to be 0.22°C/10 year for SSP1‐2.6, 0.48°C/10 year for SSP2‐4.5, 0.75°C/10 year for SSP3‐7.0, and 0.95°C/10 year for SSP5‐8.5 during 2015–2100, which is 1.4–1.6 times the warming of nonpermafrost regions. Warming rates in high latitudes are 1.2–1.7 times higher than those in high‐elevation regions. Continuous permafrost regions' warming will be 1.2–1.4 times higher than in other permafrost regions. For permafrost with high ground ice content, warming will be 1.1 times greater than in permafrost regions with medium or low ground ice content.

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Expression and localization of amelotin, laminin γ2 and odontogenesis-associated phosphoprotein (ODAPH) on the basal lamina and junctional epithelium - Cong Li; Yan Gao; Zhenzhen Xu; Yuan Tian; Haiyu Mu; Cuicui Yu; Yuguang Gao; Li Zhang (Journal of Molecular Histology, 2022)

Expression and functional analysis of cytoplasmic dynein during spermatogenesis in Portunus trituberculatus - Chao-Guang Wei; Dan-Li Mu; Dao-Jun Tang; Jun-Quan Zhu; Cong-Cong Hou (Cell and Tissue Research, 2021)

Runx2 deficiency in junctional epithelium of mouse molars decreases the expressions of E-cadherin and junctional adhesion molecule 1 - Yuan Tian; Haiyu Mu; Aiqin Wang; Yan Gao; Zhiheng Dong; Yang Zhao; Cong Li; Li Zhang; Yuguang Gao (Journal of Molecular Histology, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

A novel, validated, and plant height-independent QTL for spike extension length is associated with yield-related traits in wheat - Cong Li; Huaping Tang; Wei Luo; Xuemei Zhang; Yang Mu; Mei Deng; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2020)

Use of QSAR and SSD methods on deriving predicted no-effect concentrations in seawater and sediment for ten individual parent- and alkyl-PAHs and a case study on the assessment of their ecological risks from the Dalian Bay, China - Ying Wang; Xing Liu; Yi Cong; Jin Fei; Juying Wang; Dian Zhang; Liang Liu; Jingli Mu; Ziwei Yao (Acta Oceanologica Sinica, 2020)

A novel, major, and validated QTL for the effective tiller number located on chromosome arm 1BL in bread wheat - Jiajun Liu; Huaping Tang; Xiangru Qu; Hang Liu; Cong Li; Yang Tu; Shuiqing Li; Ahsan Habib; Yang Mu; Shoufeng Dai; Mei Deng; Qiantao Jiang; et al. (Plant Molecular Biology, 2020)

Flag leaf size and posture of bread wheat: genetic dissection, QTL validation and their relationships with yield-related traits - Jian Ma; Yang Tu; Jing Zhu; Wei Luo; Hang Liu; Cong Li; Shuiqin Li; Jiajun Liu; Puyang Ding; Ahsan Habib; Yang Mu; Huaping Tang; et al. (Theoretical and Applied Genetics, 2020)

Genetic analysis of cob resistance to F. verticillioides: another step towards the protection of maize from ear rot - Cong Mu; Jingyang Gao; Zijian Zhou; Zhao Wang; Xiaodong Sun; Xuecai Zhang; Huafang Dong; Yanan Han; Xiaopeng Li; Yabin Wu; Yunxia Song; Peipei Ma; et al. (Theoretical and Applied Genetics, 2019)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Autophagy induced by bovine viral diarrhea virus infection counteracts apoptosis and innate immune activation - Yulong Zhou; Yachao Ren; Yanlong Cong; Yu Mu; Renfu Yin; Zhuang Ding (Archives of Virology, 2017)

The N170 component is sensitive to face-like stimuli: a study of Chinese Peking opera makeup - Tiantian Liu; Shoukuan Mu; Huamin He; Lingcong Zhang; Cong Fan; Jie Ren; Mingming Zhang; Weiqi He; Wenbo Luo (Cognitive Neurodynamics, 2016)

The effects of CYP1A inhibition on alkyl-phenanthrene metabolism and embryotoxicity in marine medaka (Oryzias melastigma) - Jingli Mu; Fei Jin; Juying Wang; Ying Wang; Yi Cong (Environmental Science and Pollution Research, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

Meiofauna distribution in intertidal sandy beaches along China shoreline (18°–40°N) - Er Hua; Zhinan Zhang; Hong Zhou; Fanghong Mu; Jia Li; Ting Zhang; Bingqing Cong; Xiaoshou Liu (Journal of Ocean University of China, 2016)

Probabilistic ecological risk assessment of cadmium in the Bohai Sea using native saltwater species - Jingli Mu; Juying Wang; Ying Wang; Yi Cong; Zhifeng Zhang (Acta Oceanologica Sinica, 2014)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Aluminum ammonium sulfate dodecahydrate purified from traditional Chinese medicinal herb Korean monkshood root is a potent matrix metalloproteinase inhibitor - Yehua Shen; Sen Liu; Fenghai Jin; Tianyang Mu; Cong Li; Kun Jiang; Weihua Tian; Dahai Yu; Yingqi Zhang; Xuexun Fang (BioMetals, 2012)

Antigenic variation between Newcastle disease viruses of goose and chicken origin - Zhi-jie Li; Yang Li; Shuang Chang; Zhuang Ding; Lian-zhi Mu; Yan-long Cong (Archives of Virology, 2010)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)